Case Report: Recurrent supraglottitis in a patient with metastatic melanoma treated with ipilimumab and nivolumab - Palmeri, Marisa; Weiss, Sarah A.; Purnell, Phillip (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) are a standard of care for advanced melanoma but have the potential to cause immune-related adverse events (irAEs), which can vary widely in character and severity. Immune-related airway disease, such as supraglottitis, is a lesser-known and likely underreported irAE. More attention is needed to recognize this toxicity as delay has the potential to lead to airway compromise. Furthermore, the decision on whether to retreat after this toxicity poses a clinical challenge.Case presentationA 73-year-old woman with metastatic mucosal melanoma on ipilimumab/nivolumab presented with cough, dysphagia, and globus sensation. Video laryngoscopic evaluation diagnosed supraglottic edema, which was responsive to steroids; however, it recurred twice after ICI rechallenge with nivolumab monotherapy.ConclusionsThis case identifies supraglottitis as a rare irAE that requires prompt recognition to avoid airway obstruction. Close multidisciplinary collaboration with an otolaryngologist is imperative for early recognition and co-management. Reinitiation of immunotherapy after this irAE requires a careful assessment because underlying inflammation may persist and supraglottitis may recur. Further study should focus on the prevention of and prophylaxis for recurrent irAEs, particularly in patients whose disease is responding to ICI and may benefit from further treatment.